Synergistic Antimyeloma Activity of Dendritic Cells and Pomalidomide in a Murine Myeloma Model - Vo, Manh-Cuong; Yang, Seoyun; Jung, Sung-Hoon; Chu, Tan-Huy; Lee, Hyun-Ju; Lakshmi, Thangaraj Jaya; Park, Hye-Seong; Kim, Hyeoung-Joon; Lee, Je-Jung (Frontiers in Immunology, 2018)
We have previously shown that immunization with tumor antigen-loaded dendritic cells (DCs) and the immunomodulating drug, lenalidomide, synergistically potentiates the enhancing anti-tumor immunity in a myeloma mouse model. In this study, we investigated the immunogenicity of DCs combined with pomalidomide and dexamethasone in a myeloma mouse model. MOPC-315 cells were injected subcutaneously to establish myeloma-bearing mice. Four test groups were used to mimic clinical protocol: 1) PBS control, 2) DCs, 3) pomalidomide + dexamethasone, and 4) DCs + pomalidomide + dexamethasone. The combination of DCs plus pomalidomide and dexamethasone displayed greater inhibition of tumor growth compared to the other groups. This effect was closely related with reduced numbers of immune suppressor cells including myeloid-derived suppressor cells, M2 macrophages, and regulatory T cells, with the induction of immune effector cells such as CD4+ and CD8+ T cells, memory T cells, natural killer (NK) cells, and M1 macrophages, and with the activation of T lymphocytes and NK cells in the spleen. Moreover, the level of the immunosuppressive factor vascular endothelial growth factor was significantly reduced in the tumor microenvironment. The collective findings in the murine myeloma model suggest that tumor antigen-loaded DCs combined with pomalidomide and dexamethasone synergistically enhance anti-tumor immunity by skewing the immune-suppressive status toward an immune-supportive status.